Assessment Practice in a Self-Access Language Learning Center at Universidad Autónoma de Nuevo León - Licona Luna, Milton Raúl (2017)
This document is the result of a case study and it contains four major sections. The first section deepens in the problematic of the subject, going from the problem statement to the hypothesis, and it intends to indicate the structure of the research project. The second section displays the conceptual foundations dealing with assessment to later allow the case to be observed and evaluated with a proper theoretical basis. This section was developed throughout the second semester of the Masters’ program. The third section contains information regarding the methodology and a description of it and what it involves, additionally it displays the data analysis collected through the interviews to teachers from the case study and observations in such specific context as well as some conclusions. These activities were covered in different moments of the year 2016, which correspond to the second and third semester of the program. Finally, the fourth section states the findings observed, suggesting possible solutions, but focusing only in one (proposal), putting it into practice and discussing some recommendations for teachers in that specific context that might help others who encounter similar situations in their language classroom.